2001
DOI: 10.1159/000051575
|View full text |Cite
|
Sign up to set email alerts
|

Nevi and Melanoma: Lessons from Turner’s Syndrome

Abstract: Females with Turner’s syndrome (TS) have a markedly increased number of cutaneous nevi. While this is a well-recognized risk factor for cutaneous melanoma (CM), the incidence of this tumor in TS and the implications for our understanding of nevi and melanoma have not previously been considered. Here we report a case of an anorectal melanoma in a woman with TS and a review of the literature. Overall, there appears to be a lower than expected incidence of CM. Possible explanations are discussed and in particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 20 publications
0
14
1
Order By: Relevance
“…1,2 The defining clinical triad of impaired sexual development, webbed neck, and cubitus valgus was first described in the English-language literature by Turner 3 in 1938, with ovarian failure and streaked gonads noted in 1944. 4 Ullrich 5 in 1930 and Bonnevie 6 in 1934, described similar clinical findings in a young girl and mouse, respectively, thus, also having their names ascribed to this disorder.…”
Section: Genetics Of Turner's Syndromementioning
confidence: 99%
See 2 more Smart Citations
“…1,2 The defining clinical triad of impaired sexual development, webbed neck, and cubitus valgus was first described in the English-language literature by Turner 3 in 1938, with ovarian failure and streaked gonads noted in 1944. 4 Ullrich 5 in 1930 and Bonnevie 6 in 1934, described similar clinical findings in a young girl and mouse, respectively, thus, also having their names ascribed to this disorder.…”
Section: Genetics Of Turner's Syndromementioning
confidence: 99%
“…103,104 Interestingly, despite the prevalence of nevi, the incidence of melanoma appears to be markedly reduced in TS. 2 Only 5 cases of TS with unusual melanomas appear in the world literature, including ocular choroidal melanoma in a TS mosaic (45X/46XX), 105 lentigo maligna melanoma in a woman with 45X TS and more than 200 nevi, 97 anorectal malignant melanoma in a young women with TS and few benign nevi, 2 and 2 cases of advanced metastatic melanoma, 1 with unknown primary. 106,107 An unusual combined compound nevus/Spitz's nevus has also been reported in an 11-year-old with TS mosaic with 45 X/47XXX karyotype.…”
Section: Skin Manifestations Of Tsmentioning
confidence: 99%
See 1 more Smart Citation
“…[11], but this has been disputed by others [12]. Despite the increased number of nevi, there does not appear to be an increased risk of melanoma [13].…”
Section: Skin Manifestationsmentioning
confidence: 98%
“…I read with interest the paper of Gibbs et al [1] concerning a case of Turner's syndrome associated with mucosal melanoma. In their discussion, the authors point to the discrepancy between the large number of melanocytic nevi usually observed in sufferers from Turner's syndrome and the incidence of malignant melanoma which in these patients is deemed to be lower than expected.…”
mentioning
confidence: 99%